N-Doped carbon encapsulated molybdenum carbide as an efficient catalyst for oxidant-free dehydrogenation of alcohols. Issue 33 (10th August 2017) - Leng, Yan; Li, Jingjing; Zhang, Chenjun; Jiang, Pingping; Li, Yue; Jiang, Yuchen; Du, Shengyu
Abstract : Molybdenum carbide encapsulated in N-doped carbon was synthesized and used as an efficient heterogeneous catalyst for oxidant-free dehydrogenation of alcohols. Abstract : We report molybdenum carbide (Mo2 C) encapsulated in N-doped carbon as an efficient and stable catalyst for oxidant-free dehydrogenation of alcohols, prepared by anion exchange of H3 PMo12 O40 (PMo) with an ionic copolymer (DIM–AN) of dicationic imidazole ionic liquid and acrylonitrile, followed by a two-step carbonization at 400 °C in air and 800 °C in Ar. The synthesized catalyst (PMo@DIM–AN400/800 ) exhibits outstanding catalytic activity and selectivity for dehydrogenation of various alcohols under oxidant-free conditions and can be steadily reused at least five times for dehydrogenation of benzyl alcohol without changing its crystalline structure. The characterizations and comparative experimental results demonstrate that the active sites for dehydrogenation stem from the Mo2 C, as well as the abundant N atoms in the carbon shell, which contribute to the enhancement of catalytic performance. The strategy for the preparation of such N-doped carbon encapsulated Mo2 C using polyoxometalate-based ionic hybrids as precursors may open up new opportunities for exploring more transition-metal carbides for more catalytic applications.